Stability-Indicating HPTLC Determination of Piperine in Bulk Drug and Pharmaceutical Formulations - Singh, Anju; Jayaraman, S.; Jayaram Kumar, K.; Rani, Asha; Nema, R.K. (Asian Journal of Chemistry, 2010)
A simple, selective, precise and stability-indicating high performance thin layer chromatography method of analysis of piperine both as bulk drug and in formulations was developed and validated. The method employed TLC aluminum plates precoated with silica gel 60F-254 as the stationary phase. The solvent system consisted of toluene: ethylacetate :: 93:9. This system was found to give compact spots of piperine (Rf value of 0.10 ± 0.02). Densitometric analysis of piperine was carried out in absorbance mode at 254 nm.The linear regression analysis data for the calibration plots showed good linear relationship with r = 0.000000 with respect to peak height in concentration range of 3-4 μg per spot. The mean value ± SD of slope and intercept were 0.03, 0.1, respectively. Piperine was subjected to acid and alkali hydrolysis, oxidation and photodegradation. The drug undergoes degradation under acidic, basic, light and oxidation conditions. This indicates that the drug is susceptible to acid, base hydrolysis, oxidation and photo-oxidation. Statistical analysis proves that the method is repeatable, selective and accurate for estimation of said drug. As the method could effectively separate the drug from its degradation products, it can be employed as stabilityindicating one.